SMS Gateway Based Vacancy of Work Vocation Information System on Pamekasan Region - selia resita; achmad jauhari; Moch Kautsar Sophan (Universitas Trunojoyo Madura, 2017)
The increased growth of the society in Pamekasan from year to year is directly proportional to the number of job seekers increase continuesly. A large number of job seekers is not only due to the inadequate number of jobs, but also because of the slow and precise job information to the proper parties (the people who need jobs). Disnakertrans as an institution formed by the Government has made several attemps to minimize the number of job seekers, but until now the result obtained are not optimal, because there is no systemthat can accommodate the needs of both parties (providers and job seekers). Therefore, the research aims to create a website that accommodates data vacancies and job seekers. Later, the data is automatically going throught the process of weighting by means of the Simple Additive Weighting, this method is expected to optimize the selection of a job based on the latest education, gender, and age that has been mentioned by job seekers when registering. Once the selection process is complete, the job information is sent via SMS Gateway to job seekers. This SMS will send the job information suitable for the number of job seekers who have posted on the website.